Public Health Services: Makassar Government's response In the Early Phase of the COVID-19 - Andi Nur Fiqhi Utami; Tawakkal Baharuddin; Nur Khaerah; Citra N. Fariaty (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2022)
The Covid-19 pandemic has affected many aspects, including public health services. In this situation, the role of the government is needed to continue to strive to fulfill and ensure that health services continue to run well. This study aims to determine the government's response at the beginning of the pandemic phase and to find the inhibiting factors in fulfilling public health services in Makassar. This study also makes it possible to see how the prospects for public health services after the pandemic will be in the future. This study uses documentation data and internet data to collect relevant information. Data analysis uses a qualitative approach by maximizing the use of the Nvivo 12 Plus analysis software. The findings of this study indicate that during the COVID-19 pandemic period, public health services do not only focus on infected patients but also public health services as a whole. This causes services to be less than optimal because medical personnel and infrastructure cannot accommodate the situation. In this situation, aspects still hinder the fulfillment of public health services, including low public awareness, access to information, regulations, and the fulfillment of health facilities. The prospect of health services becomes essential in the future. This requires a more innovative and adaptive national health system.